Molluskan Hemocyanins Activate the Classical Pathway of the Human Complement System through Natural Antibodies - Pizarro-Bauerle, Javier; Maldonado, Ismael; Sosoniuk-Roche, Eduardo; Vallejos, Gerardo; López, Mercedes N.; Salazar-Onfray, Flavio; Aguilar-Guzmán, Lorena; Valck, Carolina; Ferreira, Arturo; Becker, María Inés (Frontiers in Immunology, 2017)
Molluskan hemocyanins are enormous oxygen-carrier glycoproteins that show remarkable immunostimulatory properties when inoculated in mammals, such as the generation of high levels of antibodies, a strong cellular reaction and generation of non-specific anti-tumor immune responses in some types of cancer, particularly for superficial bladder cancer. These proteins have the ability to bias the immune response towards a Th1 phenotype. However, despite all their current uses with beneficial clinical outcomes, a clear mechanism explaining these properties is not available. Taking into account reports of natural antibodies against the hemocyanin of the gastropod Megathura crenulata (KLH) in humans as well as other vertebrate species, we report here for the first time, the presence, in sera from unimmunized healthy donors, of antibodies recognizing, in addition to KLH, two other hemocyanins with documented immunomodulatory capacities: CCH and FLH (the hemocyanins from the gastropods Concholepas concholepas and Fissurella latimarginata, respectively). Through an ELISA screening, we found IgM and IgG antibodies reactive with these hemocyanins. When the capacity of these antibodies to bind deglycosylated hemocyanins was studied, no decreased interaction was detected. Moreover, in the case of FLH, deglycosylation increased antibody binding. We evaluated through an in vitro complement deposition assay whether these antibodies activated the classical pathway of the human complement system. The results showed that all three hemocyanins and their deglycosylated counterparts elicited this activation, mediated by C1 binding to immunoglobulins. Thus, this work contributes to the understanding on how the complement system could participate in the immunostimulatory properties of hemocyanins, through natural, complement-activating antibodies reacting with these proteins. Although a role for carbohydrates cannot be completely ruled out, in our experimental setting, glycosylation status had a limited effect. Finally, our data open possibilities for further studies leading to the design of improved hemocyanin-based research tools for diagnosis and immunotherapy.